2022
DOI: 10.3390/insects13100935
|View full text |Cite
|
Sign up to set email alerts
|

The Source Areas and Migratory Pathways of the Fall Armyworm Spodoptera frugiperda (Smith) in Sichuan Province, China

Abstract: The Sichuan Province, located in Southwest China, is one of China’s main maize-producing areas, and is also an important node along the north-south migratory pathways that pests follow within China. After its invasion, the fall armyworm (FAW), Spodoptera frugiperda (Smith), was found in 70.81% of all counties in Sichuan. However, FAW source areas and their migratory pathways into Sichuan remain unclear. This study simulated FAW sources and their migratory pathways into Sichuan during 2020 and 2021 using the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…For FAW, wind is an important factor in their migratory activity, as self-powered flight can only support their short-range dispersal. However, we visualized the monthly mean night atmospheric conditions from April to August at 850 hPa height ( Jiang et al., 2022 ) over the study area, and the results showed that the monthly mean wind direction blows from north to south, as shown in Figure 6 . In this study, we simulated more than 680 thousand trajectories and only 4.9% of the trajectories successfully entered the European territory probability density of FAW landing point are shown in Tables S1 , S2 .…”
Section: Discussionmentioning
confidence: 99%
“…For FAW, wind is an important factor in their migratory activity, as self-powered flight can only support their short-range dispersal. However, we visualized the monthly mean night atmospheric conditions from April to August at 850 hPa height ( Jiang et al., 2022 ) over the study area, and the results showed that the monthly mean wind direction blows from north to south, as shown in Figure 6 . In this study, we simulated more than 680 thousand trajectories and only 4.9% of the trajectories successfully entered the European territory probability density of FAW landing point are shown in Tables S1 , S2 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed based on the temporal pattern of FAW captures and migration modeling using wind transport systems that annual migrations analogous to that described in North America are occurring in southeastern Asia. Proposed pathways include migration from Myanmar into the Yangtze River Delta, then into Northern China, South Korea, and finally Japan [50][51][52][53]. While the data are suggestive that a northward migration is occurring, the identity of the source populations and the details of the migratory pathways remain speculative.…”
Section: Plos Onementioning
confidence: 99%
“…Meanwhile, being a major migratory pest, the speed at which this pest invades and spreads is concerning. After infesting Myanmar in late 2018, FAW spread to 27 Chinese provinces within a year and became a dominant pest [4,5].…”
Section: Introductionmentioning
confidence: 99%